Dictionary of science and technology over 17000 terms clearly defined - Collin S. Simon (A Bloomsbury reference book)
Offers over 17,000 terms from various areas of science and technology, including chemistry, physics and biology, earth sciences, engineering, astronomy, electronics, medicine and telecommunications. This book gives definitions for hundreds of terms, from fields such as biotechnology, computing and environmental science. This fully up-to-date second edition gives clear and concise definitions for hundreds of new terms, from fast-moving fields such as biotechnology, computing and environmental science. It`s an ideal reference for students, or anyone dealing with scientific or technical language.